Sexual Assault and Sexual Harassment in the U.S. Military Annex to Volume 2. Tabular Results from the 2014 RAND Military Workplace Study for Department of Defense Service Members - Morral, Andrew R. (RAND Corporation, 2015)
The Department of Defense Sexual Assault Prevention and Response Office asked the RAND Corporation to conduct an independent assessment of the rates of sexual assault, sexual harassment, and gender discrimination in the U.S. military. This Annex to Volume 2 contains detailed tabular results for the DoD active component from the 2014 RAND Military Workplace Study.